Body image : understanding body dissatisfaction in men, women, and children - Grogan, Sarah, 1959- (London ; New York : Routledge, 2008)
"This text provides a comprehensive review of research on body image from psychology, sociology, and gender studies in men, women, and children.
In addition to reviewing evidence for sociocultural influences on body image, the book reviews recent literature and includes new data on body-modification practices (cosmetic surgery, piercing, tattooing, and bodybuilding), and takes a critical look at interventions designed to promote positive body image. It also attempts to link body image to physical health, looking in particular at motivations for potentially health-damaging practices such as anabolic steroid use and cosmetic surgery.
1. Introduction -- 2. Culture and body image -- The idealization of slenderness -- The basis of body shape ideals -- The diet industry -- Recent cultural trends -- Summary -- 3. Women and body image -- Assessment of body image -- Behavioral indicators of body dissatisfaction -- Social construction of femininity -- Summary -- 4. Men and body image -- Assessment of body image -- Behavioral indicators of body dissatisfaction -- Social construction of masculinity -- Summary -- 5. Media effects -- Surveys relating media exposure to body image -- Studies investigating direct effects of media images on body image -- Theories of media influence -- Body shape role models -- Recent developments -- Reducing the effects of media imagery -- Summary -- 6. Age, social class, ethnicity and sexuality -- Body image across the life span -- Ethnicity and body image -- Social class and body image -- Body shape, sexual attractiveness and sexuality -- Summary -- 7. Promoting positive body image -- Psychological factors predicting positive body image -- General conclusions -- Summary.
Includes bibliographical references (p. [208]-235) and indexes.
Keywords: Body image -- Social aspects -- United States; Body image -- Social aspects -- Great Britain